A simple method of measuring the effective SRS coefficient in single-mode optical fibres and the range of its applicability. (November 2017) - Shikhaliev, I.I.; Gainov, V.V.; Dorozhkin, A.N.; Nanii, O.E.; Konyshev, V.A.; Treshchikov, V.N.
Abstract: This paper describes techniques for measuring the SRS coefficient in a wide spectral range, including the region of small Stokes shifts. A simple, approximate method is proposed for evaluating the SRS coefficient near a gain peak. Spectral dependences of the SRS coefficient are presented for various telecom fibres.